Malaysia (Application of International Law in Malaysia) - Hamid, Abdul Ghafur@Khin Maung Sein (Oxford University Press, 2019)
This chapter describes international law in Malaysia. Malaysia is unique in the sense that it amalgamates multiple characteristics: a federal state, a constitutional monarchy, and a state with a dual legal system. It is a multilateral player with active involvement in many intergovernmental organizations. In relation to international conventions, Malaysia has a policy of respecting them and complying with them. What is surprising, however, is that Malaysia rejects outright the doctrine of incorporation in respect of customary international law, deviating from the practice of the UK and other common law countries. Despite the fact that customary international law is binding on all states, and that a state will be responsible under international law for its breach, customary international law appears to be an alien law to the Malaysian courts. It appears that Malaysia is not only a dualist country, but also more dualist compared to any other common law counterparts.